Análisis bibliográfico sobre investigaciones de sistema de climatización por adsorción utilizando fuentes renovables de energía. - Proaño Aragundi, Luis Alfonso (2019)
In this research, an analysis on air conditioning system by adsorption was carried out; its importance lies in the production of cold, applied to the preservation of products, in addition to the comfort that society requires without affecting the environment. By analyzing the theoretical resources available, in order to know the trends of the development of refrigeration under the principle of adsorption, it is evident that the subject has strong attachment to ecological factors; that the pairs of adsorption are composed of two elements that adsorb and another that desorbe, that there are two types of processes, one chemical and the other physical, and that although there are contributions from various authors regarding the subject, the investigative antecedents are not sufficient. When comparing the most relevant trends, it is established that this process is conditioned mainly by pressure and temperature, that not all liquids or gases can act as adsorbates and not all have the same capacity; that there are several adsorbents and adsorbates that have been studied, and whose selection depends on several factors such as affinity, cost, integrity, toxicity, availability, among others, and its applicability is not absolute but relative to each case of application, so that it is not possible to indicate one that is optimal. The scope of the research is limited to the theoretical field without practical application.